Study and Development of Linier Low Density Polyethylene (LLDPE) and Poly Lactid Acid (PLA) Biodegradable Compouns Using Compatibizer LLDPE-g-MA - Ghozali, Muhammad; Sinaga, Pius Doni B.; Maranata, Shela; Rohmah, Elfi Nur (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2016)
This study discusses composite polymer of LLDPE and PLA at a ratio of 100: 0, 80:20, 60:40, 40:60, 20:80, 0: 100 with 4 phr LLDPE-g-MA compatibilizer. The process of making composite was performed using rheomix, which was then molded into thin sheets using hydraulic hot press to test its mechanical properties, i.e. SEM, TGA and biodegradable. The test results of mechanical properties (tensile strength and elongation at break) showed that the less the composition of PLA in the composite, the higher the mechanical properties. SEM composite test results have indicated that the LLDPE/PLA composite has a smooth surface, indicating good compatibility between LLDPE and PLA. The TGA testing produced thermal degradation in the composite sample as the PLA compositions decreased. The biodegradable test results showed that the more the PLA composition increased, the higher the missing mass of the compositesamples. Based on the test results, composite LLDPE/PLA can be used as a polybag plastic because it has strong mechanical properties and environmentally friendly due to the fact that it can be degraded by microorganisms.